In vitro and in vivo pharmaco-dynamic study of the novel fentanyl derivatives: Acrylfentanyl, Ocfentanyl and Furanylfentanyl. (15th May 2022) - Bilel, Sabrine; Azevedo Neto, Joaquim; Arfè, Raffaella; Tirri, Micaela; Gaudio, Rosa Maria; Fantinati, Anna; Bernardi, Tatiana; Boccuto, Federica; Marchetti, Beatrice; Corli, Giorgia; Serpelloni, Giovanni; De-Giorgio, Fabio; et al.
Abstract: Fentanyl derivatives (FENS) belongs to the class of Novel Synthetic Opioids that emerged in the illegal drug market of New Psychoactive Substances (NPS). These substances have been implicated in many cases of intoxication and death with overdose worldwide. Therefore, the aim of this study is to investigate the pharmaco-dynamic profiles of three fentanyl (FENT) analogues: Acrylfentanyl (ACRYLF), Ocfentanyl (OCF) and Furanylfentanyl (FUF). In vitro, we measured FENS opioid receptor efficacy, potency, and selectivity in calcium mobilization studies performed in cells coexpressing opioid receptors and chimeric G proteins and their capability to promote the interaction of the mu receptor with G protein and β-arrestin 2 in bioluminescence resonance energy transfer (BRET) studies. In vivo, we investigated the acute effects of the systemic administration of ACRYLF, OCF and FUF (0.01–15 mg/kg i.p.) on mechanical and thermal analgesia, motor impairment, grip strength and cardiorespiratory changes in CD-1 male mice. Opioid receptor specificity was investigated in vivo using naloxone (NLX; 6 mg/kg i.p) pre-treatment. In vitro, the three FENS were able to activate the mu opioid receptor in a concentration dependent manner with following rank order potency: FUF > FENT=OCF > ACRYLF. All compounds were able to elicit maximal effects similar to that of dermorphin, with the exception of FUF which displayed lower maximal effects thus behaving as a partial agonist. In the BRET G-protein assay, all compounds behaved as partial agonists for the β-arrestin 2 pathway in comparison with dermorphin, whereas FUF did not promote β-arrestin 2 recruitment, behaving as an antagonist. In vivo, all the compounds increased mechanical and thermal analgesia with following rank order potency ACRYLF = FENT > FUF > OCF and impaired motor and cardiorespiratory parameters. Among the substances tested, FUF showed lower potency for cardiorespiratory and motor effects. These findings reveal the risks associated with the use of FENS and the importance of studying the pharmaco-dynamic properties of these drugs to better understand possible therapeutic interventions in the case of toxicity. Highlights: FENT, ACRYLF OCF and FUF behave as potent selective mu agonists in calcium mobilization assay. FENT, ACRYLF and OCF behave as partial agonists for the β-arrestin 2 pathway in the BRET Assay. FUF behaves as an antagonist for the β-arrestin 2 pathway in the BRET Assay. FENT, ACRYLF OCF and FUF increased mechanical and thermal analgesia. FUF shows a monophasic motor impairment and low cardiorespiratory toxicity compared to FENT, ACRLF and OCF.